TINJAUAN YURIDIS PEGELOLAAN OBJEK WISATA PERMANDIAN DI KECAMATAN AMONGGEDO KABUPATEN KONAWE - Mutalib Saranani, Abdul (Penerbit Lafadz Jaya, 2022)
Tourism as a strategic sector and as a medium for integrating programs and activities between development sectors, is a logical consequence if tourism is determined to be the leading development that requires all Ministries to support its development. The aim of the research is to find out how local governments are in their efforts to manage bathing tourism objects in Amonggedo Species, Konawe Regency. In this study, the researcher uses a normative approach. The normative approach is intended to explore and examine laws and regulations as a basis for research. The reasons for the researcher include, among others, to refer to the typology of research, that the study of a normative approach to law conceptualizes law as norms, rules, regulations and legislation that applies at a certain time and place as a product of a certain sovereign state power.